THE EFFECT OF FREE NUTRITIOUS MEAL PROGRAM ON STUDENTS’ PHYSICAL FITNESS, GROWTH, AND LEARNING MOTIVATION IN JEPARA REGENCY - Muhammad Chanifuddin Hadiansyah; cahyo yuwono (Universitas Negeri Semarang, 2026)
This study aimed to analyze the effect of the Government Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) on students’ physical fitness, growth, and learning motivation in Jepara Regency. The MBG program represents a national strategic policy designed to enhance human resource quality through balanced nutritional intake for school-aged children. However, empirical studies examining its simultaneous impact on both physical and psychological dimensions remain limited. This research employed a quantitative approach using a pretest–posttest design. The sample consisted of 220 students from grades VII, VIII, and IX at MTs Mathalibul Huda Mlonggo, Jepara Regency, selected through purposive sampling. Physical fitness was measured using the Indonesian Physical Fitness Test (TKJI), growth status was assessed through Body Mass Index (BMI) based on height and weight measurements, and learning motivation was evaluated using a validated and reliable Likert-scale questionnaire. Data were analyzed through normality testing followed by the Wilcoxon Signed-Rank Test to determine differences before and after program implementation. The findings revealed that the Free Nutritious Meal Program had a statistically significant effect on students’ physical fitness (p < 0.05), as indicated by improved TKJI scores after the intervention. Growth indicators based on BMI categories also showed significant improvement (p < 0.05), reflecting better nutritional status. Furthermore, students’ learning motivation significantly increased (p < 0.05), suggesting that adequate nutritional intake contributed to enhanced energy levels, concentration, and academic engagement. These findings confirm that the MBG program not only improves biological outcomes such as physical fitness and growth but also positively influences psychological aspects, particularly learning motivation. Therefore, the Free Nutritious Meal Program can be considered an effective strategic intervention to support students’ health and educational quality in a holistic and sustainable manner